Nationalism, Media, and Arabic Language Instruction: Cultivating Patriotism at Islamic Universities in South Sulawesi - Bustanul Arifin, Nursyirwan; Shadriyah, Shadriyah; Mulyana, Elma (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Nationalism constitutes a critical value that must be nurtured among university students, particularly in the face of growing threats to national integration. It can be effectively internalized through educational institutions at all levels, from primary schooling to higher education. This study aims to develop instructional media and pedagogical methods grounded in digital technology, specifically Google Translate as an innovative approach to fostering national global literacy. Rather than functioning as a passive translation tool, Google Translate is integrated into a structured instructional framework designed to enhance students' Arabic language proficiency and national global literacy. The study employs a Research and Development (R&D) design with a quantitative approach, and data were analyzed using canonical correlation analysis to measure the relationship between independent and dependent variables, both simultaneously and partially. The initial hypothesis posited that the use of these instructional media and methods would significantly improve students' Arabic language proficiency and national global literacy, both simultaneously and partially. The findings indicate that, when examined simultaneously, the development of Google Translate-based instructional media and methods exerts a significant combined influence on Arabic language proficiency and national global literacy. However, at the partial level, only the development of Google Translate-based instructional methods demonstrated a significant effect on national global literacy, while the other variables did not yield statistically significant results. These findings suggest that the adoption of this instructional methodology contributes to an enhancement of students' national global literacy, which in turn reinforces their sense of nationalism and patriotism.